OP0164 BLISS-LN: A RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED PHASE 3 TRIAL OF INTRAVENOUS BELIMUMAB IN PATIENTS WITH ACTIVE LUPUS NEPHRITIS. (2nd June 2020) - Furie, R.; Rovin, B. H.; Houssiau, F.; Amoura, Z.; Santiago, M.; Contreras, G.; Malvar, A.; Mok, C. C.; Saxena, A.; Yu, X.; Teng, Y. K. O.; Barnett, C.; et al.
Abstract : Background: Lupus nephritis (LN), a serious manifestation of systemic lupus erythematosus (SLE), affects nearly 70% of patients (pts) in high-risk groups. To preserve renal function, LN requires fast and effective treatment. Despite medical advances, progression rates at 15 years to end-stage renal disease (ESRD) remain >40% for pts with diffuse proliferative LN. Belimumab (BEL), approved in pts aged ≥5 years with active SLE, improved renal parameters in pts with baseline renal involvement in a post hoc analysis of Phase 3 trials data. Objectives: To assess efficacy and safety of intravenous (IV) BEL vs placebo (PBO), plus standard therapy (ST), in pts with active LN. Methods: BLISS-LN is a Phase 3, randomised, double-blind, PBO-controlled, 104-week study (GSK Study BEL114054, NCT01639339 ). Adults with SLE and biopsy-proven LN (class III, IV, and/or V) were randomised (1:1) to monthly BEL 10 mg/kg IV or PBO, plus ST. Primary endpoint: Primary Efficacy Renal Response (PERR); defined as urine protein creatinine ratio [uPCR] ≤0.7; estimated glomerular filtration rate [eGFR] within 20% of the pre-flare value or ≥60 ml/min/1.73m 2 ; no rescue therapy) at Week (Wk) 104. Key secondary endpoints: Complete Renal Response (CRR; defined as uPCR <0.5; eGFR within 10% of the pre-flare value or ≥90 ml/min/1.73m 2 ; no rescue therapy) at Wk 104; PERR at Wk 52; time to renal-related event (defined as ESRD/doubling of serum creatinine/renal worsening/renal disease-related treatment failure) or death. Other endpoints: time to PERR/CRR sustained through Wk 104; SLEDAI-S2K score <4 points at Wk 104; safety. Results: Overall, 448 pts were randomised (efficacy: 223/group; safety: 224/group). Significantly more BEL (43%) than PBO (32.3%) pts achieved PERR at Wk 104 (OR 1.55, 95% CI 1.04, 2.32; p=0.0311). More BEL than PBO pts achieved key secondary and other efficacy endpoints (Table). Overall, 214 (95.5%) BEL and 211 (94.2%) PBO pts had ≥1 adverse event (AE); 58 (25.9%) BEL and 67 (29.9%) PBO pts had ≥1 serious AE; 29 (12.9%) pts in each group had ≥1 AE resulting in study treatment discontinuation; 4 (1.8%) BEL and 3 (1.3%) PBO pts developed on-treatment fatal AEs. Conclusion: In the largest LN study to date, data from BLISS-LN demonstrate that BEL plus ST significantly improves LN renal responses compared with ST alone with a favourable safety profile. Study funding: GSK. Disclosure of Interests: Richard Furie Grant/research support from: GSK, Consultant of: GSK, Brad H Rovin Grant/research support from: GSK, Consultant of: GSK, Frederic Houssiau Grant/research support from: UCB, Consultant of: GSK, Zahir Amoura Grant/research support from: GSK, Roche, Consultant of: GSK, Astra Zeneca, Amgen, Mittermayer Santiago: None declared, Gabriel Contreras Grant/research support from: Genentech, Merck, Consultant of: Genentech, Merck, Ana Malvar Consultant of: GSK and Roche, chi chiu mok: None declared, Amit Saxena Consultant of: GSK, AZ, BMS, Xueqing Yu: None declared, Y.K. Onno Teng Grant/research support from: GSK, Consultant of: GSK, Aurinia Pharmaceuticals, Novartis, Carly Barnett Shareholder of: GSK, Employee of: GSK, Susan Burriss Shareholder of: GSK, Employee of: GSK, Yulia Green Shareholder of: GSK, Employee of: GSK, Beulah Ji Shareholder of: GSK, Employee of: GSK, Christi Kleoudis Shareholder of: GSK, Consultant of: GSK, Employee of: Parexel, David Roth Shareholder of: GSK, Employee of: GSK